A study of some quality indicators of locally manufactured halva and its conformity with the Syrian standard specification (Damascus University Journal of agriculture sciences, 2025)
The research was carried out in 2021 in Adra Industrial Area, within a private factory for the manufacture of tahini halva, with the aim of studying some chemical indicators of the raw material used to obtain tahini, and studying some chemical indicators of the auxiliary secondary materials used in the manufacture of tahini halva locally, in addition to conducting a bacteriological study of the final product ( halva) and compare the results with the Syrian standard specification. The results of the study of the raw materials used in the production of tahini and the materials used in the manufacture of tahini halva showed their conformity with the Syrian standard specifications for these materials, as it was found that the chemical indicators of white sugar, glucose sugar and sesame tahini used in the manufacture of tahini halva were in conformity with the Syrian standard specifications. The study also showed that some of the studied tahini halva samples did not conform to the Syrian standard specification from the microbial point of view.
Keywords: Sesame; Tahini; Tahini Halva; Sucrose; Glucose; Microbial Load; Chemical Indicators